Comparative efficiency performance of SME's and other companies listed on JSE-ALTX - Makhabeni, Thokozani Wiseman (My University, 2015)
The Johannesburg Alternative Exchange is a capital market for listing small and fast growing companies. Consequently, the listing requirements on the AltX are not as onerous as on the JSE main board as they are meant to accommodate as many small businesses as possible.The problem is that it is not very clear whether the compromise listing requirements do have any impact on subsequent firm performance and therefore lead to market inefficiency resulting from the existence of information asymmetry consequently arising from the compromise listing requirements. This paper therefore investigates the efficiency performance of SMEs and None-SMEs listed on AltX. The results of this study show that SMEs have positive abnormal returns at IPO stage and at month 1 while for the months thereafter, SMEs exhibit negative abnormal returns in the short to medium term. In terms of the test of significance, SMEs have significant abnormal returns at month 2, and have significant cumulative abnormal returns from year 3- 6. None-SMEs behaved differently, for the most parts these companies have positive abnormal returns during the study period. In terms of the test of significance, None-SMEs have significant abnormal returns in month zero, and have significant cumulative abnormal returns for year 5 and year 6. The results for all the 7 year period are mixed although for the most part show that post IPO abnormal returns are not significantly different from zero, therefore one cannot reject the null hypotheses that abnormal returns and/or cumulative abnormal returns are equal to zero. In terms of cumulative abnormal returns, the results do indicate that in some cases, the cumulative abnormal returns are significantly different from zero. This is because cumulative abnormal returns vary from positive figures to negative figures which have a cancelling effect on each other.
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2015.